The impact of pelvic organ prolapse and/or continence surgery on pelvic floor muscle function in women: A systematic review. Issue 6 (25th May 2019) - Mastwyk, Sally; McClelland, Jodie; Rosamilia, Anna; Frawley, Helena
Abstract: Aims: To systematically review the evidence for the effect of pelvic organ prolapse (POP) and/or continence surgery on pelvic floor muscle (PFM) morphometry and function in women, and to investigate whether a relationship exists between PFM measures and clinician‐reported objective pelvic floor outcomes postoperatively. Methods: Six electronic databases were searched until March 2018. Studies were included if they examined the effect of POP and/or continence surgery on the PFM in women, and reported pre‐ and postoperative data. Methodological quality was assessed using a modified Downs and Black checklist. Three meta‐analyses were planned based on postoperative follow‐up time. Results: Twenty‐one studies met the inclusion criteria. Varied surgical interventions and 33 different PFM measures were represented. The methodological quality of included studies varied considerably. The 0 to 6 weeks postoperative meta‐analysis showed no statistically significant change in PFM function (SMD = 0.04; 95% confidence interval [CI] = −0.26 to 0.33). This was consistent at 3 and 6 or more months (SMD = 1.13; 0.35 95% CI = −0.34 to 2.60, − 0.42 to 1.12 respectively). None of the included studies investigated the relationship between PFM measures and clinician‐reported objective outcomes postoperatively. Conclusions: This review did not show a clear effect of POP and/or continence surgery on PFM morphometry or function in women and was unable to show a relationship with outcomes such as objective prolapse score and urodynamic findings. This could be because surgery does not measurably impact on the PFM or due to the poor quality and heterogeneity of studies. Future well‐designed research is needed to specifically investigate change in the PFM following surgery.